(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the typological features of word formation in English and the native language within a systematic comparative framework. It is shown that both languages employ key morphological processes such as derivation, compounding, and conversion [1; 2], yet they differ significantly in structural organization, productivity, and linguistic motivation. The analytic nature of English results in flexible word-formation models and multifunctional morphemes [1], whereas the native language displays a highly regular agglutinative system with transparent affixation [4]. By comparing similarities and differences in forming new lexical units, the study reveals how typological factors shape lexical enrichment, semantic development, and communicative functions in both languages [5]. The findings contribute to deeper cross-linguistic understanding and provide a theoretical basis for language teaching, translation, and lexicographical research.